Investing Back Home : Return Migration and Business Ownership in Albania - Kilic, Talip; Carletto, Calogero; Davis, Benjamin; Zezza, Alberto (2012)
This study uses data from the 2005 Albania Living Standards Measurement Study survey to assess the impact of past migration experience of Albanian households on non-farm business ownership through instrumental variables regression techniques. Considering the differences in earning potentials and opportunities for skill acquisition in different destination countries, we differentiate the impact of past household migration experience by main migrant destinations. The study also explores the heterogeneity of impact based on the timing of migration. The empirical results indicate that past household migration experience exerts a positive impact on the probability of owning a non-farm business. While one additional year in Greece increases the probability of household business ownership by roughly 6 percent, a similar experience in Italy or farther destinations raises the probability by over 25 percent. Although past household migration experience for the period of 1990-2000 is positively associated with the likelihood of owning a household enterprise, a similar association does not exist for the period of 2001-2004.